A scheme of variable separation for matrix bilinear functional equation and its use - Kalenyuk , P. I.; Nitrebich , Z. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Necessary and sufficient conditions for the solvability of a bilinear matrix functional equation are presented. The conditions are applied in the construction of the solutions of systems of partial differential equations.